Incidence of antiepileptic drug use in Parkinson's disease - Tuominen, Santeri; Tiihonen, Miia; Paakinaho, Anne; Koponen, Marjaana; Kaasinen, Valtteri; Hartikainen, Sirpa; Tolppanen, Anna-Maija (SAGE PUBLICATIONS INC, 2025)
Background: Antiepileptics are used to treat epilepsy but also, e.g., neuropathic pain, essential tremor and dystonia. It is not known whether they are more commonly used in persons with Parkinson's disease (PD).
Objective: To assess the incidence of antiepileptic use in a nationwide cohort of persons with PD before and after the diagnosis and compared the findings to a matched cohort without PD.
Methods: This register-based Finnish nationwide cohort included 18365 persons diagnosed with PD between 2001-2015. Incidence of antiepileptic initiations, from 10 years before until 10 years after the PD diagnosis, was compared to an age-, sex-, and region-matched cohort without PD.
Results: Antiepileptics were more commonly initiated for persons with PD (29.3% of PD cohort and 15.2% of comparison cohort). Gabapentinoids were the most commonly initiated antiepileptics in both cohorts. A similar pattern in initiation rates was observed for both gabapentinoids and other antiepileptics, with increased incidence in the PD cohort approximately three years before the diagnosis and a significant peak around the time of PD diagnosis (the initiation rate at the time of PD diagnosis 3/100 and 1/100 person-years, for the PD and comparison cohorts, respectively). Clonazepam initiations were more common in the PD cohort (26.7% of initiations vs. 5.8% in the comparison cohort).
Conclusions: The increase in antiepileptic initiation rates before the diagnosis of PD suggests that they might be used for prodromal motor or non-motor symptoms.